Front end of low power transmitter for wireless capsule endoscope - Lioe, De Xing; Shafie, Suhaidi; Ramiah, Harikrishnan; Sulaiman, Nasri
A low power transmitter front end for the application of a capsule endoscope operating at ISM band of 434 MHz has been proposed. The proposed architecture is aim to achieve low power consumption which is the essential parameter in a capsule endoscope. The transmitter front end is implemented using Silterra 0.13 um CMOS technology and consists of an upconversion mixer and a voltage controlled oscillator. The current consumption of the system is 1.57 mA with the supply voltage of 1.2 V. Output power is found to be -14.4 dBm and the phase noise of the ring oscillator is -81.76 dBc/Hz at offset frequency of 160 kHz.